1999
DOI: 10.1093/emboj/18.6.1539
|View full text |Cite
|
Sign up to set email alerts
|

Identification of heparin-binding EGF-like growth factor as a target in intercellular regulation of epidermal basal cell growth by suprabasal retinoic acid receptors

Abstract: The role of retinoic acid receptors (RARs) in intercellular regulation of cell growth was assessed by targeting a dominant-negative RARα mutant (dnRARα) to differentiated suprabasal cells of mouse epidermis. dnRARα lacks transcriptional activation but not DNAbinding and receptor dimerization functions. Analysis of transgenic mice revealed that dnRARα dose-dependently impaired induction of basal cell proliferation and epidermal hyperplasia by all-trans RA (tRA). dnRARα formed heterodimers with endogenous retino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 42 publications
12
71
1
Order By: Relevance
“…Other studies confirmed that HB-EGF mRNA was markedly induced by RA in normal human keratinocytes and normal mouse skin 11-13 . Chapellier's study also demonstrated a positive correlation between HB-EGF expression and RA-induced proliferation, further supporting the hypothesis that HB-EGF could be a paracrine factor synthesized in the suprabasal layers that mediates RA-induced hyperplasia 12,13 . In human skin, HB-EGF and amphiregulin have been reported to activate epidermal growth factor receptor (EGFR) and mediate retinoid-induced epidermal hyperplasia 14 .…”
Section: Introductionsupporting
confidence: 53%
“…Other studies confirmed that HB-EGF mRNA was markedly induced by RA in normal human keratinocytes and normal mouse skin 11-13 . Chapellier's study also demonstrated a positive correlation between HB-EGF expression and RA-induced proliferation, further supporting the hypothesis that HB-EGF could be a paracrine factor synthesized in the suprabasal layers that mediates RA-induced hyperplasia 12,13 . In human skin, HB-EGF and amphiregulin have been reported to activate epidermal growth factor receptor (EGFR) and mediate retinoid-induced epidermal hyperplasia 14 .…”
Section: Introductionsupporting
confidence: 53%
“…In situ hybridization analysis indicated that topical tRA treatment of normal mouse skin induces HB-EGF mRNA expression exclusively in suprabasal keratinocytes (Xiao et al, 1999). To confirm this, we analyzed the expression of HB-EGF in this process using a different technique.…”
Section: Resultsmentioning
confidence: 95%
“…Although the mechanism by which retinoids regulate the proliferation of epidermal cells is not completely understood, it has been shown that treatment of normal adult human skin and keratinocytes with tRA not only leads to thickening of the skin but also induces significant expression of several genes including HB-EGF (Bernard et al, 2002;Stoll and Elder, 1998;Varani et al, 2001). Induction of HB-EGF has also been reported in the skin of mice treated topically with tRA (Chapellier et al, 2002;Xiao et al, 1999). These studies suggested that HB-EGF might be involved in the signaling cascades underlying retinoid-induced epidermal hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…In the HaCaT human keratinocyte cell line we demonstrated that the human Has2 gene is also a primary EGF and all-trans-RA responding gene. Although retinoids are applied in the therapy of various skin diseases, so far only a few primary RA responding genes have been established in human keratinocytes (33). Therefore, the 8-fold induction of Has2 mRNA after only 2 h treatment with all-trans-RA (Fig.…”
Section: Discussionmentioning
confidence: 99%